2020
DOI: 10.32394/pe.74.29
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid supplementation in pregnancy and prevention of fetal neural tube defects

Abstract: INTRODUCTION. Folic acid deficiency in very early pregnancy significantly increases the risk for neural tube defects in the developing fetus. Due to very high demands for folic acid in pregnancy, adequate supply is not possible without dietary supplements. AIM OF THE STUDY. Evaluation of the frequency and adequacy of folic acid supplementation before and during pregnancy among women from the Warsaw region of Poland. MATERIAL AND METHODS. The study was conducted among 100 pregnant women using direct interviewin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Food supplements were more often used by pregnant women and those planning to become pregnant (89 and 56%, respectively) (34). Frequent food supplement consumption was also observed in another study in the group of women during pregnancy and women becoming pregnant (82 and 41%, respectively) (35). In our study pregnant women were not included.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Food supplements were more often used by pregnant women and those planning to become pregnant (89 and 56%, respectively) (34). Frequent food supplement consumption was also observed in another study in the group of women during pregnancy and women becoming pregnant (82 and 41%, respectively) (35). In our study pregnant women were not included.…”
Section: Discussionsupporting
confidence: 63%
“…Data on food supplement use in Poland vary depending on the group. Surveys of the representative population for the country: from 2000 (29) and described in this manuscript from 2019-2020 showed a lower proportion of supplement users than surveys of target groups (31)(32)(33)(34)(35). However, the differences in data may be due to the fact that some authors could include OTC drugs containing vitamins and minerals into supplements.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Another study shows that 42% of the surveyed women took folic acid before pregnancy. When pregnant, folic acid was supplemented by 83% of women, of which 71% started as late as the fifth-sixth week of pregnancy and beyond [25]. Meanwhile, a survey among female non-medical students (N = 325) showed that in 2008, 35.3% of them were aware of the importance of periconceptional folic acid supplementation, and in 2013, the figure reached 41.1% [26].…”
Section: Introductionmentioning
confidence: 99%